PROTOTIPE PENGONTROLAN RUNNING TEXT MENGGUNAKAN VOICE DAN ARDUINO UNO VIA SMARTPHONE ANDROID - Ferry Sudarto; Moch Ibnu safari; Muhammad Fazri (Universitas Raharja, 2017)
Running text or commonly known as text running a medium to deliver information that is most often encountered as a means of advertising that are informative. Running text display is generally in the form of LED-LED are connected and assembled into a row of LED or may be a dot matrix. Submission of information by displaying the running text has not been effective and efficient in terms of use. There are still shortcomings that enable people to experience vision errors and too long waiting for the text to be displayed. Thus the necessary tools to deliver information that can work optimally to minimize shortages by designing a control tool running text using voice (voice) and arduino uno. This tool uses a series of android smartphones facilities to provide input sound is converted into a data string and compiled in arduino using serial communications, and will be displayed on the LED Dotmatrix as output. Submission of information by using running text that comes with using sound can improve efficiency and effectiveness in the use and also the time required so that it can reduce the level of difficulty of the user in receiving the information